Support to women who denounce experiences of violence based on her social network - Letícia Becker Vieira; Ivis Emília de Oliveira Souza; Florence Romijn Tocantins; Florentina Pina-Roche (Universidade de São Paulo, 2015)
Objective: to analyze the possibilities of help/support through the mapping and acknowledgement of the social network of women who denounce experiences of violence at a Police Precinct for Women.Method: qualitative study based on the theoretical-methodological framework of Lia Sanicola's Social Network, through interviews with 19 women.Results: the analysis of the network maps evidenced that the primary social network was more present than the secondary on and, despite consisting of significant relations, it demonstrates limitations. The women access the secondary network occasionally in the violence problem and/or its repercussions in their life and health. The discrete presence of the health network in the composition of the social network was revealed and, when mentioned, the relation between the health professional and the woman was characterized as fragile.Conclusion: the importance of the social network relates to the creation of spaces of help/support for the women beyond the moment of the aggression, which accompany them throughout their process of emancipation from an experience annulled by violence, considering that each woman acts and makes decisions in the relational context when she is ready for it.